2009
DOI: 10.1063/1.3226882
|View full text |Cite
|
Sign up to set email alerts
|

Yield strength of tantalum for shockless compression to 18 GPa

Abstract: Effect of temperature, strain, and strain rate on the flow stress of aluminum under shock-wave compression J. Appl. Phys. 112, 073504 (2012); 10.1063/1.4755792Comparative studies of yield strength and elastic compressibility between nanocrystalline and bulk cobalt Modeling of the elastic precursor behavior and dynamic inelasticity of tantalum under ramp wave loading to 17 GPa A magnetic loading technique was used to study the strength of pure, annealed, and cold-rolled polycrystalline tantalum under planar ram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 61 publications
(123 reference statements)
4
32
1
1
Order By: Relevance
“…In contrast, after a cold rolling treatment, no evidence of twining is observed (Figure 4a-b), although the microstructure has a significant number of long, low angle boundaries present. c) In a previous work [8] (also noted by others [7,9]) it was observed that the upper and low yield points at the HEL were removed by cold rolling. It was suggested that this was due to an accumulation of interstitial oxygen atoms around dislocations, effectively pinning them in place, and thus requiring a high stress to remove them.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…In contrast, after a cold rolling treatment, no evidence of twining is observed (Figure 4a-b), although the microstructure has a significant number of long, low angle boundaries present. c) In a previous work [8] (also noted by others [7,9]) it was observed that the upper and low yield points at the HEL were removed by cold rolling. It was suggested that this was due to an accumulation of interstitial oxygen atoms around dislocations, effectively pinning them in place, and thus requiring a high stress to remove them.…”
Section: Resultsmentioning
confidence: 77%
“…For example, a reduction in stacking fault energy in fcc metals (either in a pure metal like silver [4], or via alloying in copper alloys [5]) can result in a shift in deformation mechanism from dislocation formation to twinning, whilst in bcc metals, a reduction in Peierls stress (such as in niobium) can result in a much higher proportion of the deformation being accommodated by dislocation generation rather than motion of pre-existing dislocations [6]. The effects of increasing dislocation density before shock loading has been much less studied, although a series of papers have reported on the role of dislocation density on tantalum [7][8][9]. In this paper, we examine the effects of dislocation density on the shock response of two near ideal fcc and bcc metals, copper and tantalum.…”
Section: Introductionmentioning
confidence: 99%
“…Tantalum has a high density (16.65 g/cm 3 ), melting temperature (2996 0 C) and is unique in it's combination of high hardness with high plasticity. Extensive research and publications are dedicated to investigations of the elastic-plastic properties and spall fracture of tantalum under shock-wave loading [5][6][7][8][9], but the question about the influence of structural factors on these processes remains unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…Ramp wave loading of annealed and cold worked tantalum has been carried out by Asay et al using magnetic induction techniques [11]. Their work is one of the few that allow direct comparison between independent strength measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Histories for shocked tantalum are shown in Fig. 3 a) [11,12]. In annealed tantalum the stress rises to a precursor peak known as the isentropic elastic limit (IEL) by analogy with the Hugoniot Elastic Limit (HEL).…”
Section: -3mentioning
confidence: 99%